High sulphur activated carbon regeneration - Powell, Christopher (2023)
Companies such as CPL Ltd, who specialise in the production and regeneration of activated carbon, are looking at ways in which they can reduce their impact on the climate by switching to greener methods for their operations. At current, their aim is to move towards producing more regenerated activated carbon rather than procuring virgin carbonaceous material such as coal. However, their current regeneration method, a conventional thermal method, entails long processing times which require vast amounts of fossil fuels and consume large quantities of energy. Additionally, the regeneration of spent sulphurous activated carbon via thermal regeneration results in the production of sulphuric and sulphurous acids, which cause structural damage to their equipment and present a health & safety issue with their workforce. The company have been looking into possible replacement methodologies including the use of microwave technology, with the hope that the volumetric and selective heating involved can reduce their carbon footprint and reduce/eliminate the production of unwanted by-products.